Current status of highly pathogenic avian influenza and its range expansion in China - ZHANG Zhi-cheng; LI Chang-you; HUANG Bao-xu; Mao Zhen-bin (浙江大学学报. 农业与生命科学版)
Based on GIS techniques, and integrating with risk assessment theory, the current status of HPAI (highly pathogenic avian influenza) occurrence and its range expansion pattern in China were explored. The result showes that: ①the strength of current status of HPAI occurrence in China was diminished along with the national comprehensives control strategy, but the risk of mutation and its further range expansion still existed.②Pattern analysis show that multi-epidemic centre of HPAI occurrences in China have been come into shaped, which could be specifically loomed at the epidemic centre of West-south & east-south wetlands, Yangzte river wetlands, Tibet wetlands, Xingjiang wetlands, Gan-meng wetlands and Heilongjiang wetlands, and the corridors role of HPAI ranges in those given regions mentioned above can loom significantly along with local dominated small scaled feeding & breeding pattern in the years coming.③Regional pattern analysis show that the disease was cluster-distributed in Yunnan, Tibet, Xingjiang, Inner-Mongolia, and Liaoning Province, the spatial significant associations within these given regions make the HPAI reoccur possible in the future.